Where's the beef: how one woman navigated advertising's male-dominated creative world. Issue 5 (4th July 2022) - Olsen, Katie
ABSTRACT: While much light is shone on issues when women are unable to achieve leadership positions in advertising, less attention is afforded to examining the paths of those women who were able to be successful when the odds were against them. This study dives deep into the experiences of one woman who was named Executive Creative Director at one of the leading independent full-service agencies in the lower US Midwest at the age of 33, promoted to Chief Creative Officer at age 36, all while married and a mother to two young children. When more than 70% of advertising's creative leaders are male, this swift travel along a professional path that is historically tough for women warranted an exploration of her experiences and relationships. Power, feminism and support systems were found to be in play across the findings. Encouragement from women throughout her life helped provide the confidence needed; a commitment to maintaining a strong marriage and a healthy work-life balance were identified as having the biggest impact on her success. This study's influence reaches from strategic communication curriculum in higher education all the way to industry leaders, working to close advertising's creative gender gap through education and awareness.